Modern approaches to forming of culture of paternity in cooperating of preschool educational establishment with a young family (Pedagogy of Higher and Secondary Education, 2013)
Vakhnyak N. V. Modern approaches to forming of culture of paternity in cooperating of preschool educational establishment with a young family.In the article modern approaches of teachers of preschool educational establishment are exposed to forming of culture of paternity of young families, basic parameters of pedagogical culture, certainly levels of formed of culture of paternity, the stages of pedagogical education of young families are selected.
Keywords: culture of paternity; pedagogical education; preschool educational establishment; young family